THE EFFECT OF PROFITABILITY, COMPANY GROWTH, BUSINESS RISK, MANAGERIAL OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON DEBT POLICY IN SUB-MINING COMPANIES COAL SECTOR LISTED ON THE IDX - Heri Susan; Jummaini; Marzuki; Zulfan (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to determine the effect of profitability, company growth, business risk, managerial ownership, and institutional ownership on debt policy in mining companies listed on the Indonesia Stock Exchange. The data used in this study are secondary data from 16 mining companies listed on the Indonesia Stock Exchange. The method used to analyze the relationship between the independent variables and the dependent variable is the panel data regression method. The results of the study indicate that profitability has a positive and significant effect on debt policy in coal mining companies listed on the Indonesia Stock Exchange. Company growth has a positive and significant effect on debt policy. Business risk has a negative and significant effect on debt policy. Managerial ownership has no significant effect on debt policy. Institutional ownership has no significant effect on debt policy. Overall, profitability, company growth, business risk, managerial ownership, and institutional ownership have a positive and significant effect on debt policy.